A bone to pick : the good and bad news about food, along with wisdom, insights, and advice on diets, food safety, GMOs policy, farming, and more - Bittman, Mark (Clarkson Potter, 2015)
"Mark Bittman made headlines three years ago when it was revealed that, for the first time, the New York Times opinion page would feature a food writer to help us make sense of the tangled webs of food, health, environment, politics, and culture. As an opinion columnist, Mark has delighted us, enraged us, and inspired us to do more for ourselves and our world with the same no-nonsense style. In the tradition of his NYT bestselling Food Matters, this book collects the best of his columns, updated to reflect the latest research, and tied together with new material to give context and show how far we've come in just a few years. What emerges is a collection that shows us the story of who we are as a nation of cooks, eaters, and voters right now"--